Microhardness and microstructure of aluminium alloy 5052 by high-pressure torsion process and subsequent annealing - Ahmad Muhammad Aziz,; Intan Fadhlina Mohamed,; Mohd Zaidi Omar,; Zainuddin Sajuri,; Norinsan Kamil Othman,; Mohammad Azlan Aripin,; Nor Kamaliana Khamis,; Hawa Hishamuddin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The grain refinement by high-pressure torsion (HPT) process and high-temperature stability have been studied in a commercial non-heat-treated aluminium alloy, 5052. The HPT process was conducted on 10 mm disks of the alloys at room temperature with an applied pressure of 6 GPa for 5 and 10 turns with a rotation speed of 1 rpm. The HPT processing leads to microstructural refinement with an average grain size of ~188 nm and ~156 nm for 5 turns and 10 turns with an increased value of dislocation density. The Vickers microhardness test was performed at 100 gf for a duration of 15 s. It was found that the hardness increased from the onset of straining and saturated at approximately 165 Hv after processing at both 5 and 10 turns. The samples were then annealed at high temperatures. The study demonstrated that annealing at 200 °C for 1 h reduced the hardness by 30% in both samples and enlarged the gain sizes to 226 nm. The results indicated that the rate of hardness decrease is faster in 10 turns compared with 5 turns thus explaining the higher kinetic annihilation phenomenon observed in higher straining in 10 turns due to the higher stored energy in the grains.